PENGARUH MEDIA SOSIAL DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN PADA SIRUP JERUK KALAMANSI PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KABUPATEN BENTENG. - Ratnawili, Ratnawili; Endahka W, Nahda Adilah (UM. Bengkulu, 2024)
This study aims to determine the effect of service quality and location on purchasing decisions in the three brothers' calamansi citrus business. This type of research is a type of quantitative descriptive research, the object of this research is consumers in the business of three brothers Kalamansi orange syrup in Bengkulu city. The sampling method is accidental sampling technique. The number of respondents in this study were 170 respondents. The data collection method is using questionnaires. Data analysis techniques using multiple linear regression analysis and hypothesis testing, namely the t test and f test. The results of this study can be concluded that simultaneously product quality and social media have a positive and significant effect on consumer buying interest decisions. Partially the three social media variables, product quality and consumer buying interest have an influence on consumer buying interest. The better the quality of the products provided and Social Media which can increase the decision of a sustainable Consumer Purchase Interest. Keywords : social media, product quality and consumer buying interest.